Co(II), Ni(II), Cu(II), Zn(II) Cd(II) and Pd(II) Complexes of Acetic Acid and Phenyl Acetic Acid Hydrazones of 2-Aminonicotinaldehyde - Swamy, B.; Ramanuja Swamy, J. (Asian Journal of Chemistry, 2010)
Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Pd(II) complexes of tridentate Schiff base ligands derived from the condensation of acetic acid hydrazides, with 2-aminonicotinaldehyde have been synthesized. These complexes have been characterized based on analytical, molar conductance, magnetic susceptibility, thermal, electronic and ESR spectral studies.